Behaviour of steel fiber reinforced concrete & high performance concrete exposed to elevated temperature - Sahara, Mohd Sarif (2018)
Steel fiber reinforced concrete (SFRC) and high performance concrete (HPC) are widely used in the structural elements of buildings such as slabs, industrial floors and others by enhancing the mechanical properties of structural elements of buildings. Generally, high temperature is serious problems for all concrete structures which drive in a mechanical decay of the concrete and even damaging effects at the structural level due to exposure to the flames, in case of fire. In this experimental work has an aspect which focused on basic mechanical behavior of concrete at high temperature including residual strength. After being subjected to different elevated heating temperatures, ranging between room temperature and 240ºC, the compressive strength of concrete reinforced with 4% steel fiber reinforced concrete (SFRC) and high performance concrete (HPC) residual strength have been investigated. For each type of concrete 18 sets for plain concrete (PC), high performance concrete (HPC) and steel fiber reinforced concrete (SFRC) of cubes have been cast. These specimens have been tested for compressive strength at elevated temperatures of room temperature and 240ºC for one hour in hot condition immediately after taking out from oven. The results are analysed and final conclusion are drawn.